1991
DOI: 10.1089/sct.1991.7.29
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Clinical and Pharmacokinetic Study of Intracarotid Cisplatin and Bleomycin

Abstract: Fifteen patients with progressive primary malignant or metastatic brain tumors were treated on a clinical and pharmacokinetic study with intracarotid cisplatin and bleomycin. Toxicity was tolerable and consisted mainly of nausea and vomiting. Neurologic toxicity included focal seizures (1), leukoencephalopathy (1), and motor weakness (1). Five patients had improvement in CT scans and four patients had stabilization of disease. Recommended dosage for future clinical trials are cisplatin 60 mg/m2 and bleomycin 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Previous reports of intraarterial chemotherapy have described a wide range of complications depending on the infusion protocol, agent used, and catheterrelated technique (10,12,14,15,21,31,32).…”
Section: Analysis Of Complicationsmentioning
confidence: 99%
“…Previous reports of intraarterial chemotherapy have described a wide range of complications depending on the infusion protocol, agent used, and catheterrelated technique (10,12,14,15,21,31,32).…”
Section: Analysis Of Complicationsmentioning
confidence: 99%
“…Several trials combining BCNU and IA CDDP have been reported with survival times ranging from 8 weeks to 48 months for responders [17][18][19][20][21]. CDDP intraarterially has also been associated with bleomycin [22], BCNU and VM-26 [23], and etoposide [24]. The response rate in these trials ranged from 28% to 82% with survival times from 33 to 160 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The CNS toxicity and lack of efficacy associated with the intra-carotid delivery of nitrosoureas in phase II studies (12) lead to the evaluation of less lipophilic though "active" agents or combinations of agents (carboplatin, cisplatin, bleomycin , etoposide, TNF-alpha) delivered by the intra-carotid route for the treatment of malignant glioma (13)(14)(15)(16)(17).…”
Section: Intra-carotid Delivery Of Chemotherapymentioning
confidence: 99%